2023
DOI: 10.1002/adom.202202711
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection and Cellular Photothermal Therapy via a Self‐Photothermal Modulation Biosensor

Abstract: The use of light, which is s a powerful tool for imaging and sensing, has also become one of the most prospective strategies in tumor treatment. Optical microfibers, which have engineerable waveguiding properties, are highly attractive for optical sensing and photothermal therapy on the micro/nanoscale. However, for their real‐world application, the sensitivity limit needs to be addressed, as does the issue of improving the intrinsic photothermal performance of silica microfibers. Herein, a nanointerface consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Later in 2019, Zhou et al demonstrated a gold-nanorod-MNF coupled system for relative humidity sensing, and achieved a spatial resolution of 1.5 mm [414] . Meanwhile, such photon-plasmon coupled MNF systems have also served as an effective platform for biosensing [441,511,512] . For example, in 2019 Li et al functionalized the surface of a 7.1μm-diameter MNF with a plasmonic nanointerface consisting of black-phosphorus-supported gold nanohybrids [510] .…”
Section: Surface Functionalized Mnf Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Later in 2019, Zhou et al demonstrated a gold-nanorod-MNF coupled system for relative humidity sensing, and achieved a spatial resolution of 1.5 mm [414] . Meanwhile, such photon-plasmon coupled MNF systems have also served as an effective platform for biosensing [441,511,512] . For example, in 2019 Li et al functionalized the surface of a 7.1μm-diameter MNF with a plasmonic nanointerface consisting of black-phosphorus-supported gold nanohybrids [510] .…”
Section: Surface Functionalized Mnf Structuresmentioning
confidence: 99%
“…demonstrated a gold-nanorod-MNF coupled system for relative humidity sensing, and achieved a spatial resolution of 1.5 mm [414] . Meanwhile, such photon-plasmon coupled MNF systems have also served as an effective platform for biosensing [441,511,512] . For example, in 2019 Li et al .…”
Section: Mnf-based Applicationsmentioning
confidence: 99%
“…Xiao et al designed a silicon dioxide microfiber combined with Au@Ag 2 S nanomaterials, which enhanced the sensitivity of the sensor to temperature and was able to distinguish hepatocellular carcinoma cells from normal cells and kill the cancerous cells by photothermal heat. 88 Yin et al used mesoporous silica as an intermediate layer and ferric iron tetroxide as the core, and CdTeS quantum dots as fluorescent labeling agent, which can detect and destroy cancer cells more perfectly. 89 Of course the coupling of silica and gold nanomaterials is very common, Seo et al synthesized GNR@SiO 2 nanoparticles to enhance their near-infrared light absorption.…”
Section: Photothermal Materials Applied To Ctcs Detectionmentioning
confidence: 99%